PENERAPAN STANDAR OPERASIONAL PROSEDUR PADA PELAYANAN PENERBITAN SURAT PERSETUJUAN BERLAYAR KAPAL PERIKANAN DI PELABUHAN PERIKANAN SAMUDERA CILACAP PROVINSI JAWA TENGAH - Rahel Angel R. Silaban; Syaifuddin Syaifuddin; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbtracOne of the public service in Cilacap Fishing Port is the issuance of port clearance. Port clearance must be owned by  fishing vessels as the requirement for fishing activites. The public service must be implemented with a Standard Operating Procedure (SOP) based on Indonesia’s Ministry of Marine and Fisheries. This study aims to determine wheter the port clearance’s service has implemented according to the SOP or not and to find out the level of service quality of the port clearance’s service by using Servqual’s concept. This research was conducted at Cilacap Fishing Port using purposive sampling method by spreading questionnaire for 43 respondents. Descriptive’s Analysis based on the respondent's answers obtained through questionnaires distributed by researcher. The result of this research shows that the port clearance’s service has implemented  SOP about 98,62% and service quality is 99,46% or very good.Key word : Port Clearance, Standard Operating Procedure, Service Quality, Fishing Port,  and Fishing Vessel.